Epidemiology: instrument the nurse's work process? - Prado, Marta Lenise do (Revista da Escola de Enfermagem da USP, 1994)
This paper discusses the role of the epidemology in the nurse's work process. It searches for the comprehension of the work process's concepts and their elements deriving from a marxist analysis. It discusses the importance of this comprehension for the knowledge / recognition of the nursing profession and the epidemologic support question as a work instrument.